Pemanfaatan Potensi Lokal Sebagai Desa Wisata di Lingkungan Lerek, Gombengsari - Deva Rachman; Imamatut Ta'dzimah; M. Syahrul Mubarok; Candra Bhakti Susilo; Nadya Artika Maulani; Mohammad Isfironi (Universitas Serang Raya, 2025)
To advance regional development and people's welfare, active community involvement is needed through the development of tourist villages. Gombengsari Village, especially the Lerek Neighborhood, has abundant local potential. Therefore, it is hoped that the community can take advantage of this local potential to advance the previously conceptualized tourist village further. This community service implementation uses the PAR method, in which the relevant parties must be actively involved. The activities include identifying local potential, introducing local potential to elementary school-age children, and discussions with MSME actors. Based on the activities above, it is known that the potential that exists in the Lerek Environment is the potential for education-based tourism (edutourism), namely education about coffee and milking etawa goats. MSMEs also play an important role in village tourism, namely utilizing natural resources and advancing the village economy. After joint discussions, MSME players realized that choosing packaging and labeling was very important to attract consumers to buy their products. Apart from that, several MSME players are also interested in marketing their products to e-commerce.